Understanding College Students’ Phone Call Behaviors Towards a Sustainable Mobile Health and Well-Being Solution - Kim, Yugyeong (2021)
During the transition from high school to on-campus college life, students leave home and start facing enormous life changes, including meeting new people, taking on more responsibilities, being away from the family, and dealing with academic challenges. These changes lead to an elevation of stress and anxiety, affecting students’ health and well-being. With the help of smartphones and their rich collection of sensors, we can continuously moni tor various factors that affect students’ behavioral patterns, such as communication behaviors associated with their health, well-being, and academic success. In this work, we try to assess college students’ communication patterns (in terms of phone call duration and frequency) that vary across various geographical contexts (e.g., dormitories, class buildings, dining halls) during different times (e.g., epochs of a day, days of a week) using visualization techniques. The findings from this work will help foster the design and delivery of smartphone-based health interventions, thus helping the students adapt to the changes in life.